Sports, exercise and nutritional genomics: Current status and future directions - Barh, Debmalya; Ahmetov, Ildus I. (London Elesvier Inc., 2019)
Sports, Exercise, and Nutritional Genomics: Current Status and Future Directions is the first reference volume to offer a holistic examination of omics-driven advances across different aspects of exercise and sports physiology, biochemistry, sports medicine, psychology, anthropology, and sports nutrition; and highlighting the opportunities towards advance personalized training and athlete health management.